In-Hospital Death and the Change of the Grave Trajectory: The Cosmological Meanings of Sadness in Moroccan Context during the COVID-19 Pandemic - Ahmed, Hougua Ben; Fatima, Idrissi Khaoulani; Hasna, Bichraden (Al-Jami'ah Research Centre, 2023)
This study examines the institutional changes and topographical landmarks within which the incident of death took place in the Moroccan context by focusing on the topic of in-hospital death during the COVID-19 pandemic. The complicated aspects surrounding the death arise from the process of medicalization, burial, and mourning among the relatives of the deceased. Methodologically, the research is based on a grounded phenomenological analysis of the experiences of relatives (50 participants) who lost their deaths in the first wave of the pandemic in four Moroccan cities: Rabat, Kenitra, Fez, and Missour. The study concludes that the negative attitude of Moroccans towards in-hospital death does not stem from the fragility of health services or the characteristics of loneliness and isolation, as revealed by Norbert Elias’s sociology. However, it closely links to the anthropological factors that construct the personal concept in the Moroccan context as a knot of relationships and looks at the body in its social, cultural and cosmological extensions.[Penelitian ini mengkaji perubahan institusional dan landmark topografis tempat terjadinya kematian dalam konteks masyarakat Maroko dengan fokus kematian di rumah sakit selama pandemi COVID-19. Aspek rumit kematian muncul selama proses penanganan medis, penguburan, dan perkabungan di antara kerabat almarhum. Secara metodologis, penelitian ini didasarkan pada analisis fenomenologis terhadap pengalaman 50 orang dari keluarga orang yang meninggal pada gelombang pertama pandemi COVID-19 di empat kota di Maroko: Rabat, Kenitra, Fez, dan Missour. Tulisan ini menyimpulkan bahwa sikap negatif masyarakat Maroko terhadap kematian di rumah sakit tidak berasal dari buruknya layanan kesehatan atau pun dari dampak isolasi dan rasa kesepian yang khas, seperti yang diungkapkan sosiologi Norbert Elias. Namun, sikap negatif tersebut erat terkait dengan faktor antropologis yang mengkonstruksi konsep personal dalam konteks masyarakat Maroko yang menjadi simpul hubungan sosial dan pandangan terhadap jasad dalam konteks sosial, budaya, dan kosmologi.]